EFFICACY AND SAFETY OF HERBAL AND ALTERNATIVE MEDICINE - Amal Saleh Faraj, Noura Hassan Safi, Wedad Mohammed Alshammary, Sultan Eid Amer Al Otaibi, Turki Mohammed Alsaffar, ‏ Norah Fahad Al Hasinah, Abdullah Sfoug Alanazi, ‏Mona Melhey AlHarbi, Mazi Mubahhil Ibrahim Alshammari, Houson Ali Aloudah; Adil Mohammad Ali Alolaiwi, Hamad Hassan Tamim Aldawsari, Ahmed Hammad Alshammari (Chelonian Research Foundation, 2022)
The use of herbal medicine (HM) is increasing on a global scale. Single herb preparations, as well as ethnic and contemporary herbal medicine formulations, are often used as supplementary treatments or to enhance the overall well-being of consumers. Previous research provides a concise overview of prevalent patterns in the use of HM as a supplementary or alternative form of medicine, the training of healthcare practitioners and individuals, and the existing and planned regulations governing the production of HM. We examine the possible interactions between herbal medicines (HMs) and both other HMs and pharmaceutical drugs, which may result in serious side effects if HMs are used without appropriate supervision from medical professionals. Several significant issues have emerged because to the consistent worldwide expansion in the utilization of HM. Interaction between herbal medicine (HM) and conventional medicines (CD) may lead to either underdosing of CD or unpleasant responses. Similarly, interaction between different herbal supplements might result in harmful effects of the formulations. Insufficient knowledge among healthcare professionals and patients about the therapeutic characteristics of herbal medicines has to be addressed at both regional and global levels in order to guarantee the safety of consumers. Keywords: herbal medicine, conventional medicines, safety, efficacy, ethnic and contemporary herbal medicine.